Center-based l1-clustering method - Sabo, Kristian (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider the l1-clustering problem for a finite data-point set which should be partitioned into k disjoint nonempty subsets. In that case, the objective function does not have to be either convex or differentiable, and generally it may have many local or global minima. Therefore, it becomes a complex global optimization problem. A method of searching for a locally optimal solution is proposed in the paper, the convergence of the corresponding iterative process is proved and the corresponding algorithm is given.
Keywords: l1-clustering; data mining; optimization; weighted median problem